Histopathology of nasopharyngeal and palatine tonsils in Japanese black calves naturally infected with Mycoplasma bovis - AHMED, Amaal Ezzat; NAKAI, Mutsumi; KAKIYA, Miho; FUKE, Naoyuki; HEGAZY, Asmaa A; KONDO, Hiroaki; HIRAI, Takuya (Journal of Veterinary Medical Science, 2025)
Mycoplasma bovis (M. bovis) is an important bacterium in the bovine respiratory disease complex (BRDC), which causes significant economic losses. The nasopharyngeal and palatine tonsils are mucosal-associated lymphoid tissue components that are the initial barrier to respiratory pathogens. In the present study, we investigated 5 pneumonic Japanese black and 3 control calves (2 Japanese black and 1 Holstein). The localization of M. bovis in the nasopharyngeal, palatine tonsils, and lungs was examined using nested and multiplex polymerase chain reaction (PCR), histopathology, and in situ hybridization (ISH) techniques. Nested PCR revealed that all examined tissues from all pneumonic calves were positive for M. bovis infection, but not the control. Histopathology revealed suppurative nasopharyngeal tonsillitis and palatine tonsillar cryptitis in all cases. Surprisingly, prominent histologic changes were observed in the palatine tonsils but not in the nasopharyngeal tonsils. Necrotizing suppurative bronchopneumonia was observed in 4 pneumonic calves. In ISH analysis, positive hybridization signals adherent to and/or within the surface epithelium of nasopharyngeal tonsils and crypt epithelium of nasopharyngeal and palatine tonsils were observed. Additionally, these signals were seen in the palatine tonsillar cryptic detritus. In the lungs, ISH signals were observed in necrotic areas, the bronchial epithelium, and pulmonary inflammatory exudate. These findings suggest that the nasopharyngeal and palatine tonsils are the primary sites of M. bovis infection. Also, M. bovis can colonize the detritus in the crypts of the palatine tonsils of the pneumonic animals.